Electric Conductivity, Permittivity (Capacitance), Acoustic Loss and Quality Factors of Triglycine Sulphate Crystal (Isomorphs) with External Biasing - Upadhyay, T.C.; Nautiyal, Ashish (Asian Journal of Chemistry, 2011)
In external biasing, electric capacitance (permittivity), quality factor, acoustic attenuation and electric conductivity of pyroelectric, triglycine sulphate crystal (TGS) whose chemical structure is (NH2CH2COOH)3H2SO4. This centrio-symmetric crystal and its isomorphs have been studied by two sub-lattice pseudospin lattice coupled mode (PLCM) model or vibration model which is extended with third and fourth order phonon an-harmonic interaction and electric field terms. In-homogeneity of this pseudospin lattice coupled mode model has been solved by the use of double time, temperature dependent Green's function with renormalized boundary conditions. For better results in dielectric permittivity (capacitance), quality factor, electric conductivity and acoustic attenuation of triglycine sulphate crystal we combine pseudospin lattice coupled mode model with a different theoretical model that is Ising spin model of ferroelectrics. By the collaboration of these two theoretical models, we can predict about, physical and physio-chemical properties of triglycine sulphate crystal with best experimental supports.